2020
DOI: 10.3390/ma13020475
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Mesoporous Mn–Ce–Ti–O Aerogels by a One-Pot Sol–Gel Method for Selective Catalytic Reduction of NO with NH3

Abstract: Novel Mn–Ce–Ti–O composite aerogels with large mesopore size were prepared via a one-pot sol–gel method by using propylene oxide as a network gel inducer and ethyl acetoacetate as a complexing agent. The effect of calcination temperature (400, 500, 600, and 700 °C) on the NH3–selective catalytic reduction (SCR) performance of the obtained Mn–Ce–Ti–O composite aerogels was investigated. The results show that the Mn–Ce–Ti–O catalyst calcined at 600 °C exhibits the highest NH3–SCR activity and lowest apparent act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…For FeFe@Ti, the diffraction peaks at 25.28, 37.80, 48.05, 53.89, 55.06, 62.69, 68.76, 70.31, 75.03, and 82.66° corresponded to the anatase TiO 2 (PDF # 21-1272) (101), (004), (200), (105), (211), (204), (116), (220), (215), and (224) crystal planes, respectively. , The diffraction peaks at 33.15 and 35.61° were attributed to the (104) and (110) crystal planes of hematite Fe 2 O 3 (PDF #33-0664), respectively. , For the MnFe, the diffraction peaks at 18.84, 23.12, 32.92, 42.92, and 55.14° were ascribed to the (200), (211), (222), (402), and (044) crystal planes of Mn 2 O 3 (PDF #24-0508), respectively. , The diffraction peaks at 35.61 and 62.45° were attributed to the (110) and (214) crystal planes of hematite Fe 2 O 3 (PDF #33-0664), respectively. , It was clear that the MnFe catalyst had a weaker diffraction peak, which indicated that the Mn 2 O 3 and Fe 2 O 3 species had better dispersion properties. For MnFe@Ti, the diffraction peaks at 25.28, 37.80, 48.05, 53.89, 55.06, 62.69, and 75.03° corresponded to anatase TiO 2 (PDF #21-1272) (101), (004), (200), (105), (211), (204) and (215) crystal planes, respectively. , The diffraction peaks at 35.61° were attributed to the (110) crystal planes of hematite Fe 2 O 3 (PDF #33-0664). , The diffraction peaks at 42.92° were ascribed to the (402) crystal plane of Mn 2 O 3 (PDF #24-0508). , The high intensity of the diffraction peaks of anatase TiO 2 and the decrease of the diffraction peaks of the Mn 2 O 3 and Fe 2 O 3 indicated that the Mn 2 O 3 and Fe 2 O 3 species were coated with the TiO 2 shell layer. In addition, as shown in Figure S4, the XRD patterns before and after the MnFe@Ti reaction were compared.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For FeFe@Ti, the diffraction peaks at 25.28, 37.80, 48.05, 53.89, 55.06, 62.69, 68.76, 70.31, 75.03, and 82.66° corresponded to the anatase TiO 2 (PDF # 21-1272) (101), (004), (200), (105), (211), (204), (116), (220), (215), and (224) crystal planes, respectively. , The diffraction peaks at 33.15 and 35.61° were attributed to the (104) and (110) crystal planes of hematite Fe 2 O 3 (PDF #33-0664), respectively. , For the MnFe, the diffraction peaks at 18.84, 23.12, 32.92, 42.92, and 55.14° were ascribed to the (200), (211), (222), (402), and (044) crystal planes of Mn 2 O 3 (PDF #24-0508), respectively. , The diffraction peaks at 35.61 and 62.45° were attributed to the (110) and (214) crystal planes of hematite Fe 2 O 3 (PDF #33-0664), respectively. , It was clear that the MnFe catalyst had a weaker diffraction peak, which indicated that the Mn 2 O 3 and Fe 2 O 3 species had better dispersion properties. For MnFe@Ti, the diffraction peaks at 25.28, 37.80, 48.05, 53.89, 55.06, 62.69, and 75.03° corresponded to anatase TiO 2 (PDF #21-1272) (101), (004), (200), (105), (211), (204) and (215) crystal planes, respectively. , The diffraction peaks at 35.61° were attributed to the (110) crystal planes of hematite Fe 2 O 3 (PDF #33-0664). , The diffraction peaks at 42.92° were ascribed to the (402) crystal plane of Mn 2 O 3 (PDF #24-0508). , The high intensity of the diffraction peaks of anatase TiO 2 and the decrease of the diffraction peaks of the Mn 2 O 3 and Fe 2 O 3 indicated that the Mn 2 O 3 and Fe 2 O 3 species were coated with the TiO 2 shell layer. In addition, as shown in Figure S4, the XRD patterns before and after the MnFe@Ti reaction were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Three peaks were attributed to Mn 2+ , Mn 3+ , and Mn 4+ , respectively. 37,55 The Mn 2p 1/2 spectrum could be ascribed to 651.93, 653.10, and 654.36 eV. The three peaks were also attributed to Mn 2+ , Mn 3+ , and Mn 4+ , respectively.…”
Section: Structure Of the Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…5(B)(b), we can see that the broad peak at 580 °C can be interpreted as the overlapping of the reduction of the Ti-C,N and Mn 3 O 4 → MnO. 61 Compared with (a), the two reduction peaks of (b) shift to low temperature, which confirms that Ti-C,N promotes the redox ability of Mn-Ce/Ti-C,N. 62 The H 2 -TPR result of Mn-Ce-Co x /Ti-C,N catalysts are shown in Fig.…”
Section: H 2 -Tpr Analysismentioning
confidence: 91%